2021
DOI: 10.1016/j.scs.2021.103089
|View full text |Cite
|
Sign up to set email alerts
|

Treating two pandemics for the price of one: Chronic and infectious disease impacts of the built and natural environment

Abstract: Compact walkable environments with greenspace support physical activity and reduce the risk for depression and several obesity-related chronic diseases, including diabetes and heart disease. Recent evidence confirms that these chronic diseases increase the severity of COVID-19 infection and mortality risk. Conversely, denser transit supportive environments may increase risk of exposure to COVID-19 suggesting the potential for contrasting chronic versus infectious disease impacts of community design. A handful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…5,6 Government city planning policies specify land uses and related taxation; fund and provide transport infrastructure and other public services; regulate housing, industry, car use, and transport fares; and foster economic development. Given the challenges of the 21st century, it is essential that city planning produces cobenefits for prevention of com municable and non-communicable diseases [7][8][9][10] and climate action. 11,12 Much of the urban growth anticipated by 2050 is expected to occur in low-income and middle-income countries (LMICs), 13 which are disproportionately affected by the global burden of disease and face the harshest consequences of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Government city planning policies specify land uses and related taxation; fund and provide transport infrastructure and other public services; regulate housing, industry, car use, and transport fares; and foster economic development. Given the challenges of the 21st century, it is essential that city planning produces cobenefits for prevention of com municable and non-communicable diseases [7][8][9][10] and climate action. 11,12 Much of the urban growth anticipated by 2050 is expected to occur in low-income and middle-income countries (LMICs), 13 which are disproportionately affected by the global burden of disease and face the harshest consequences of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity levels and dietary patterns are major predictors of chronic disease risk, including cardiovascular diseases, hypertension, some cancers, and type 2 diabetes, in part through obesity (1‐3). Recent evidence has suggested that obesity or having a chronic disease increases the risk of COVID‐19‐related mortality (4). Increased time spent at home has resulted in a heightened awareness of how our home environment impacts our health.…”
Section: Introductionmentioning
confidence: 99%
“…Source: authors. Variable Reference literature Key finding(s) Exposure International air connectivity ( Findlater & Bogoch, 2018 ); ( Keita, 2020 ) Air travel is leading to an increase in the frequency of reach of infectious diseases, more connected countries have higher exposure Participation in international trade ( Ibarrarán, Ruth, Ahmad, & London, 2009 ); ( Wiedmann & Lenzen, 2018 ) Increased dependency on global network can have ripple effect in different countries, developing countries appear to be disproportionately affected Air pollution ( Fattorini & Regoli, 2020 ); ( Frontera, Cianfanelli, Vlachos, Landoni, & Cremona, 2020 ) Chronic atmospheric pollution is likely to favor the spread of COVID-19 Comorbidity ( Wang, Li, Lu, & Huang, 2020 ); ( Sanyaolu et al, 2020 ) People with comorbidity are more like to be severely affected by COVID-19 Susceptibility Population Density ( Ahmadi, Sharifi, Dorosti, Ghoushchi, & Ghanbari, 2020 ); ( Bhadra, Mukherjee, & Sarkar, 2021 ); ( Liu, Liu, & Guan, 2021 ) The spread of COVID-19 is positively correlated to population density Poverty ( Mamun & Ullah, 2020 ); ( Alkire, Dirksen, Nogales, & Oldiges, 2020 ) Poor people are more susceptible to the socio-economic impacts of COVID-19 Health ( Egawa et al, 2018 ); ( Frank & Wali, 2021 ) Healthier communities are more resilient to disaster risk, life expectancy is an important indicator of disaster risk Informality ( Wilkinson, 2020 ); ( ...…”
Section: Methodsmentioning
confidence: 99%